Plantas de las familias Lamiaceae, Asteraceae y Malvaceae, utilizadas en la medicina tradicional mexicana con propiedades antibacterianas - Espadas-Uc, Joseph A.; Velázquez-Collí, Sharon A.; Cob-Calan, Nubia N.; Moo-Puc, Juan A.; Loeza-Concha, Henry; Us-Camas, Rosa (TIP Revista Especializada en Ciencias Químico-Biológicas, 2025)
In Mexico, medicinal plants have been integral to pre-Hispanic cultures since ancient times. Studies of the Lamiaceae, Asteraceae, and Malvaceae families have identified species with antibacterial properties, which represents a promising alternative for combating resistant bacteria that cause human disease and a source of new chemical compounds helpful in repairing the damage caused by these microorganisms. This review focuses on studies of the antibacterial activity of plants from the aforementioned families used in traditional Mexican medicine against gram-positive (+) and gram-negative (-) bacteria. It also provides a brief botanical description of some of these plants, including their uses, structural components, and types of extracts with bactericidal activity, inhibited bacterial strains, zone of inhibition, and minimum inhibitory concentration (MIC). Finally, a description of the identified compounds with antibacterial potential and their possible mechanisms of action is provided.